AMP-activated protein kinase protects against necroptosis via regulation of Keap1-PGAM5 complex. (15th May 2018) - Wang, Yi-Shu; Yu, Peng; Wang, Yong; Zhang, Jing; Hang, Wei; Yin, Zhi-Xian; Liu, Gang; Chen, Jianfeng; Werle, Kaitlin D.; Quan, Cheng-Shi; Gao, Hang; Zeng, Qinghua; et al.
Abstract: Background: The AMP-activated protein kinase (AMPK) plays critical roles in growth regulation and metabolism reprogramming. AMPK activation protects cells against apoptosis from injury in different cell and animal models. However, its function in necroptosis remains largely unclear. Methods and results: In the current study, we demonstrated that AMPK was activated upon necroptosis induction and protected mouse embryonic fibroblasts (MEFs) and cardiomyocytes from N -methyl- N ′-nitro- N -nitrosoguanidine (MNNG) and reactive oxygen species (ROS) induced necroptosis. Activation of AMPK with chemicals A-769662, 2-deoxyglucose (2-DG), and metformin or constitutively active (CA) AMPK markedly decreased necroptosis and cytotoxicity induced by MNNG. In contrast, AMPK inhibitor compound C, dominant negative (DN) AMPK, as well as AMPK shRNAs increased necroptosis and cytotoxicity induced by MNNG. We further showed that AMPK physically associated with a protein complex containing PGAM5 and Keap1 whereby facilitating Keap1-mediated PGAM5 ubiquitination upon necroptosis induction. The AMPK agonist metformin ameliorated myocardial ischemia and reperfusion (IR) injury and reduced necroptosis through down-regulating the expression of PGAM5 in the Langendorff-perfused rat hearts. Conclusion: Activation of AMPK protects against necroptosis via promoting Keap1-mediated PGAM5 degradation. Metformin may act as a valuable agent for the protection of myocardial ischemia and reperfusion injury by activating AMPK and reducing necroptosis. Highlights: AMPK is activated upon necroptosis inductions. Activation of AMPK facilitates Keap1-mediated PGAM5 ubiquitination. AMPK protects against necroptosis in vitro and in vivo. Metformin ameliorates myocardial IR injury by activating AMPK.